2020
DOI: 10.1080/15412555.2020.1782867
|View full text |Cite
|
Sign up to set email alerts
|

Living with Advanced Chronic Obstructive Pulmonary Disease: A Qualitative Interview Study with Patients and Informal Carers

Abstract: The disease trajectory in chronic obstructive pulmonary disease (COPD) is characterised by a progressive decline in overall function, loss of independence and reduction of health-related quality of life. Although the symptom burden is high and care is often demanding, patients' and informal carers' experiences in living with advanced COPD are seldom described. This study sought to explore patients' and informal carers' experiences in living with advanced COPD and to understand their awareness about palliative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Eight studies reported that having a self-inflicted disease generates feelings of self-blame, shame, and guilt in people with COPD. 28 , 30 , 31 , 33 , 34 , 36 , 37 , 41 Six studies found that using a medical device (eg, inhaler or oxygen) and experiencing COPD symptoms (eg, breathlessness or uncontrollable coughing) in public cause feelings of embarrassment. 28 , 31 , 33 , 35 , 40 , 43 Three studies pointed out that people with COPD suffer from negative emotions (eg, feelings of being losers, anger, grief, fear, anxiety, depression, sadness, uselessness, or hopelessness) because their smoking resulted in an incurable disease.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies reported that having a self-inflicted disease generates feelings of self-blame, shame, and guilt in people with COPD. 28 , 30 , 31 , 33 , 34 , 36 , 37 , 41 Six studies found that using a medical device (eg, inhaler or oxygen) and experiencing COPD symptoms (eg, breathlessness or uncontrollable coughing) in public cause feelings of embarrassment. 28 , 31 , 33 , 35 , 40 , 43 Three studies pointed out that people with COPD suffer from negative emotions (eg, feelings of being losers, anger, grief, fear, anxiety, depression, sadness, uselessness, or hopelessness) because their smoking resulted in an incurable disease.…”
Section: Resultsmentioning
confidence: 99%
“… 36 , 41 In addition, people with COPD who continue smoking have feelings of being a failure or a loser. 34 , 36 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations